Peranan Lifestyle terhadap Kejadian Pra-Diabetes di Kota Makassar - Kadek Ayu, Erika; Ilhamjaya, Patellongi; A. Mushawwir, Taiyeb (bionature, 2010)
Impaired Glucose Tolerance (IGT) is defined as an early phase of Diabetic Type-2 process. IGT shows an occurance of early phase of Diabetic and asymptomatic. The prevalence is increased in accordance to poor or unhealthy lifestyle such as over consuming of carbohydrate and lack of physical excercises. The aim of the study was to analyze the correlation between lifestyle and individual with obesity, obesity and pre-diabetic, and lifestyle with pre-diabetic.The study was conducted at the Kassi-Kassi Public Health Center in Makassar from May to July 2009. The study was a case control study. The number of samples was 54 people selected by purposive sampling. The sampling were divided into 27 pre-diabetic individuals and 27 individuals with normal blood glucose. The data were collected through structured interview and questionnaire. The measurement of height, weight, waist circumference, blood pressure, and blood samples was done twice after fasting 12 hours for fasting blood glucose and oral glucose tolerance test. The data were analyzed by using univariate, bivariate with chi square, and independet t-tes and Mann-Whitney test. The result of the study indicate that lifestyle has a role in the incident of pre-diabetic in which p = 0,021.Lifestyle has been proved affecting pre-diabetic event trought obesity. This research shows a correlation between lifestyle and obesity, and also connection between obesity and pre-diabetic incident.